Barokah Deposit as a Superior Product for Collecting Funds at Bank Jatim Syariah KCP Probolinggo - Husnul Khotimah; Aprilia Dwi Jayanti (Universitas Nurul Jadid, 2025)
This study aims to examine the role of Barokah Deposits as a leading product in fundraising activities at Bank Jatim Syariah KCP Probolinggo. The research method used is qualitative with a descriptive approach. Data collection was carried out through observation, interviews, and documentation during the implementation of student practicum activities from November to December 2025. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the operations of Bank Jatim Syariah KCP Probolinggo have been carried out in a structured, systematic, and well-documented manner in accordance with Islamic banking regulations. The implementation of administration, archive management, and internal control systems have been effective in maintaining data accuracy and transparency. In addition, cash management and fundraising activities, including the Barokah Deposit product, have been carried out in accordance with Islamic principles and regulations. Barokah Deposits, which use the mudharabah contract and profit-sharing system, play a significant role in increasing customer trust and contributing to the growth of third-party funds. Thus, Barokah Deposits can be considered a leading product that is managed professionally and sustainably.